Thirty-Day Outcomes of Young and Middle-Aged Adults Admitted with Severe COVID-19 in Uganda: A Retrospective Cohort Study - Kyagambiddwa, Tonny; Kintu, Timothy Mwanje; Miiro, Emmanuel; Nabalamba, Franchesca; Asiimwe, Gloria Suubi; Namutebi, Anne Marion; Abeya, Fardous C; Lumori, Boniface A; Ijuka, Isaac; Muhindo, Rose K; Mutekanga, Andrew; Musinguzi, Richard; et al. (Infection and Drug Resistance, 2023)
Background: There is scarcity of data regarding young and middle-aged adults hospitalized with severe Corona Virus Disease 2019 (COVID-19) in Africa. In this study, we describe the clinical characteristics and 30-day survival among adults aged 18 to 49 years admitted with severe COVID-19 in Uganda. Methods: We reviewed treatment records of patients admitted with severe COVID-19 across five COVID-19 treatment units (CTU) in Uganda. We included individuals aged 18 to 49 years, who had a positive test or met the clinical criteria for COVID-19. We defined severe COVID-19 as having an oxygen saturation <94%, lung infiltrates >50% on imaging and presence of a co-morbidity that required admission in the CTU. Our main outcome was the 30-day survival from the time of admission. We used a Cox proportional hazards model to determine the factors associated with 30-day survival at a 5% level of significance. Results: Of the 246 patient files reviewed, 50.8% (n = 125) were male, the mean ± (standard deviation) age was 39 ± 8 years, majority presented with cough, 85.8% (n = 211) and median C-reactive protein (interquartile range) was 48 (47.5, 178.8) mg/L. The 30-day mortality was 23.9% (59/246). At admission, anemia (hazard ratio (HR): 3.00, 95% confidence interval (CI), 1.32–6.82; p = 0.009) and altered mental state (GCS <15) (HR: 6.89, 95% CI: 1.48–32.08, p = 0.014) were significant predictors of 30-day mortality. Conclusion: There was a high 30-day mortality among young and middle-aged adults with severe COVID-19 in Uganda. Early recognition and targeted management of anemia and altered consciousness are needed to improve clinical outcomes
Keywords: COVID-19; Uganda; Mortality; Young and middle-aged adults